Pengaruh Senam Ergonomik Berbasis Spiritual Terhadap Perubahan Tekanan Darah Lansia Penderita Hipertensi Di Kelurahan Jebres - Indriyani Ayu Mandira; Erika Dewi Noorratri (Tribhuwana Tunggadewi University, 2022)
Physiological changes experienced by the elderly with getting older then the function of the body's organs will also decreased, such as Health problems experienced by the elderly in the cardiovascular system that result in hypertension. Hypertension is often referred to as the